Product Variety as a Basis for Differentiation and Its Managerial Implications in Wholesalin - Didit Darmawan; Ayu Margareta (CV. Ulil Albab Corp, 2026)
This literature study examines product variety as a differentiation strategy in the wholesale market, focusing on how variety configuration creates competitive advantage and its managerial implications. The analysis reveals that successful differentiation requires balancing breadth and depth of product lines according to target segment characteristics. Product variety generates value when it simplifies buyer procurement processes, builds trust through consistent quality, and enhances shopping experience. Managerial implications encompass two critical areas: customer relationship strengthening through reliable stock availability and transaction convenience, and operational efficiency through process standardization and integrated information systems. The study contributes theoretically by extending differentiation literature to the wholesale sector, an area previously dominated by retail and manufacturing perspectives. Practically, it provides a conceptual framework for wholesale managers to design product portfolios that balance differentiation goals with operational capabilities. Future empirical research is recommended to quantitatively test relationships between variety dimensions and business performance across different wholesale contexts.